1993
DOI: 10.1172/jci116184
|View full text |Cite
|
Sign up to set email alerts
|

Clonal expansion of lung V delta 1+ T cells in pulmonary sarcoidosis.

Abstract: Sarcoidosis is a multisystem disease of unknown etiology characterized by the presence of noncaseating granulomas in involved tissues. To investigate a potential role for y/6 T cells in the pathogenesis of pulmonary sarcoidosis, we studied lung and blood T cells from patients for preferential expression of particular 'y/6 T cell receptors. An abnormally high percentage of 'y/6 cells was found in the blood of some patients. However, the increased percentage did not reflect an increase in absolute number, and ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
36
1

Year Published

1993
1993
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 57 publications
2
36
1
Order By: Relevance
“…It is probable that distinct antigens can precipitate sarcoidosis or sarcoidosis-like diseases in susceptible individuals. An antigen-driven process is also consistent with the oligoclonal restriction of CD41 T cells seen in sarcoidal granulomas (15)(16)(17).…”
supporting
confidence: 66%
“…It is probable that distinct antigens can precipitate sarcoidosis or sarcoidosis-like diseases in susceptible individuals. An antigen-driven process is also consistent with the oligoclonal restriction of CD41 T cells seen in sarcoidal granulomas (15)(16)(17).…”
supporting
confidence: 66%
“…In addition, many examples of clonal T-cell expansion in tumorinfiltrating lymphocytes in patients with tumors and autoimmune diseases have been reported (58 -60). Furthermore, clonal expansion of T/␥␦-lymphocytes has been reported to occur in granulomatous diseases such as sarcoidosis and tuberculosis, and some of our cases (data not shown) fell in this category (61,62). Conversely, the failure to detect a clonal population in an immunomorphological and clinical context highly suggestive of a malignant process (in approximately 10 -20% of malignant lymphoid proliferations) should be interpreted with caution.…”
Section: Discussionmentioning
confidence: 67%
“…One further study demonstrated a restricted V/~I repertoire in the peripheral blood of certain patients with rheumatoid arthritis but not in four healthy controls (30). However, it is worth noting that a recent report of preferential Vis1-J81 junctional repertoires in sarcoidosis, demonstrated a repetitive sequence in cDNA from the PBL of one of the normal control (31).…”
Section: Discussionmentioning
confidence: 94%
“…In the present work, we have shown that V81-J81junctions, while displaying the extensive alterations of germline sequences that are characteristic of post fetal stages (14), are not randomly represented among PBL V/$1 + cells in a large fraction of healthy donors. The description of such repeated sequences in the PBL of healthy donors is unprecedented since only a few V81-J81 sequences have been published to date (28)(29)(30)(31). Two studies showed an unrestricted repertoire in PBL from patients and normal controls, but predominant sequences in acute multiple sclerosis (29) and leprosy lesions (28), respectively, suggesting in situ selection of particular VIS1 + cells by so far undefined antigens.…”
Section: Discussionmentioning
confidence: 99%